The Political Business Cycles of EU Accession Countries - Mark Hallerberg; Lúcio Vinhas de Souza (Tinbergen Institute, 2000)
This paper considers whether political business cycles exist in Eastern European accession countries.Section I introduces the overall objectives of the work. Section II provides a short introductionto the political business cycle literature. It also considers the role of exchange rates, capitalmobility, and central bank independence in restricting or encouraging political business cycles.Section III lays out the accession process to date as well as the exchange rate regimes accessionstates have used. Section IV tests empirically whether there have been political business cyclesduring the time period 1990 to 1999 for the 10 Eastern European accession countries, with estimationsbased on a Mundell-Fleming model. It finds that countries with flexible exchange rates have loosermonetary policies in election years than in non-election years in countries with dependent centralbanks. If a country has a fixed exchange rate regime, it manipulates its economy in election yearsthrough running larger budgets instead of through looser monetary policy. Section V concludes withsome policy implications for the European Union's enlargement process and EMU.
Keywords: 330; Politischer Konjunkturzyklus; EU-Mitgliedschaft; Osteuropa